Detection of AXL expression in circulating tumor cells of lung cancer patients using an automated microcavity array system. (30th January 2020) - Ikeda, Mio; Koh, Yasuhiro; Teraoka, Shunsuke; Sato, Koichi; Kanai, Kuninobu; Hayata, Atsushi; Tokudome, Nahomi; Akamatsu, Hiroaki; Ozawa, Yuichi; Akamatsu, Keiichiro; Endo, Katsuya; Higuchi, Masayuki; et al.
Abstract: Noninvasive diagnostics using circulating tumor cells (CTCs) are expected to be useful for decision making in precision cancer therapy. AXL, a receptor tyrosine kinase is associated with tumor progression, epithelial‐to‐mesenchymal transition (EMT), and drug resistance, and is a potential therapeutic target. However, the epithelial markers generally used for CTC detection may be not enough to detect AXL‐expressing CTCs due to EMT. Here, we evaluated the detection of AXL‐expressing CTCs using the mesenchymal marker vimentin with a microcavity array system. To evaluate the recovery of cancer cells, spike‐in experiments were performed using cell lines with varying cytokeratin (CK) or vimentin (VM) expression levels. With high CK and low VM‐expressing cell lines, PC‐9 and HCC827, the recovery rate of AXL‐expressing cancer cells was 1%‐17% using either CK or VM as markers. Whereas, with low CK and high VM‐expressing cell lines, MDA‐MB231 and H1299, it was 52%‐75% using CK and 72%‐88% using VM as a marker. For clinical evaluation, peripheral blood was collected from 20 non–small cell lung cancer patients and CTCs were detected using CK or VM as markers in parallel. Significantly more AXL‐expressing single CTCs were detected in VM‐positive than CK‐positive CTCs ( P < .001). Furthermore, CTC clusters were identified only among VM‐positive CTCs in 20% of patients. Patients with one or more prior treatments harbored significantly more VM‐positive AXL‐expressing CTCs, suggesting the involvement of these CTCs in drug resistance. These results indicate the necessity of integrating mesenchymal markers with CTC detection and this should be further evaluated clinically. Abstract : We established the detection of AXL‐expressing in circulating tumor cells of lung cancer patients incorporating vimentin as a CTC marker in addition to cytokeratin. Significantly more AXL‐expressing CTCs were detected in patients who had prior treatment history than those did not, suggesting the involvement of AXL in drug resistance.